Factors Influencing Perceptions of Sport Coach Performance: A Scoping Review - Yusup, Novandi Firdaus; Prabowo, Trisnar Adi; Azhari, Haeruddin; Ari, M. Azy’ (UNIB Press, 2025)
This study aims to identify and map the factors that influence the perception of sports coach performance based on published research results. The research design used is a scoping review, which allows researchers to explore key concepts and existing empirical evidence, while identifying gaps in the literature. The literature was obtained through a systematic search in the PubMed, Scopus, ProQuest, and Google Scholar databases, with keywords such as